Pembuatan Website Untuk Sistem Keamanan Loker Dengan Fingerprint ID dan RFID Berbasis Website - Vargas Pratama; Egi Tri Saputra; Irwan Irwan; Zanu Saputra (Politeknik Manufaktur Negeri Bangka Belitung, 2026)
Lockers commonly used in daily life, both in public and private spaces, are generally still conventional and rely on metal keys for security. However, physical keys often cause problems such as being lost or misplaced. With the rapid advancement of technology, many devices can now be integrated with digital systems, including lockers frequently used by the public. Therefore, this project aims to develop a locker security system based on fingerprint and RFID technology integrated with a website, in order to enhance both security and user convenience. The system utilizes a fingerprint sensor for user authentication and RFID as an additional access card. The ESP32 microcontroller serves as the data processor and transmits information to the website. The website is developed using PHP as the main backend language and Bootstrap as the frontend framework to create a responsive and visually appealing interface. The development process applies the waterfall model, consisting of requirement analysis, design, implementation, and testing stages. Testing is carried out using the black-box method. The test results show that the system successfully improves security and convenience through dual-layer protection using fingerprint and RFID. In addition, the integrated website allows administrators and users to monitor user data and locker usage history efficiently.